Методологічні підходи до управління підприємством в умовах конвергенції у ринкові інститути в контексті теорії відкритої економічної системи - Рижакова, Г. М.; Рубцова, О. С. (Ways to Improve Construction Efficiency, 2012)
Generalized problem and approaches to management of enterprises as open economic system. The relation of the results of economic entities on the openness of their economic system, criteria and characteristics of its classification.